2017
DOI: 10.3390/su9071146
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Current Microgrid Policies, Incentives and Barriers in the European Union, United States and China

Abstract: Continuously increasing demand of microgrids with high penetration of distributed energy generators, mainly renewable energy sources, is modifying the traditional structure of the electric distribution grid. Major power consumer countries are looking for alternative energy sources to avoid the impact of higher fossil fuel consumption. Thus, different policies have been promulgated to promote renewable energy technologies (RETs) and distributed energy resource (DER) deployment and are encouraging technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 48 publications
0
71
0
Order By: Relevance
“…Microgrids can either be operated independently [6], as isolated grids, or as community microgrids, [7] with self-contained electricity supply systems that serve certain electric loads. There are some barriers of microgrids [8] which limit their unrestricted use.…”
Section: State Of the Artmentioning
confidence: 99%
“…Microgrids can either be operated independently [6], as isolated grids, or as community microgrids, [7] with self-contained electricity supply systems that serve certain electric loads. There are some barriers of microgrids [8] which limit their unrestricted use.…”
Section: State Of the Artmentioning
confidence: 99%
“…In addition, the authors discussed different policy interventions (e.g., financial incentives, carbon tax, minimum renewables) that have been considered in microgrid feasibility studies. In [5] the authors reported the recent perspectives, barriers, and policies for distributed energy sources in the European Union, United States, and China. Additionally, a comprehensive review of the governmental regulations affecting the deployment of microgrids in abovementioned countries was presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the next decade, it is expected that the developing economies mainly located in sub-Saharan Africa, Central and Southern Asia, and South America will face significant challenges in achieving the ambitious goals of providing access to clean energy to all people and delivering universal access to electricity [1,2]. Despite the remarkable progress on the rural and urban electrification rates around the world [3,4], and on the increasing number of innovative technologies suitable for off-grid applications, there are various factors that have hampered the success of national and local electrification projects, namely infrastructure, technical, economic, market, policy, and regulatory barriers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The current regulatory process is complex due to the amalgamation of different existing rules and regulations that are not particularly suitable for microgrids [310]. Although they are designed to maintain standard operations during a disturbance in a microgrid [311], the high connection fees are the main burden for microgrid operators [312]. Also, the islanding operation, one of the most-cited features of microgrids, creates conflict with existing rules and regulations as it has a large effect on the power supply of a grid utility.…”
Section: Challenges Of Microgridsmentioning
confidence: 99%